Loving God… unto death: The witness of the early Christians - Rosell, Sergio (HTS teologiese studies, 2010)
The article focuses on the social and theological dynamics that drove early Christ-followers to understand martyrdom as being a legitimate and honourable way by means of which to demonstrate love for God to the uttermost limits. Martyrdom is rooted much earlier in the Jewish tradition, though it received new impetus from the second century AD onwards. The study seeks to trace its raison d’être within the pages of the New Testament, both in the sayings of Jesus and the letters of Paul. It is argued that the apostle’s theology of suffering provided sufficient grounds for such an understanding, which finds in Ignatius, Bishop of Antioch, one of its major representatives. Finally, the study seeks to reflect on the plausible actualisation of non-bloody martyrdom for today’s Christian discipleship, if it has any relevance at all.